Preparation method and detection method of material capable of being used for indirectly detecting acrylonitrile gas
By preparing Zn-doped γ-Al2O3 matrix material and dispersing Pt and Pd particles on its surface, combined with electrochemical sensors to detect nitric oxide concentration, the problem of real-time monitoring of acrylonitrile gas is solved, and efficient and stable acrylonitrile gas is achieved Detection reduces costs and avoids cross-interference.
Patent Information
- Application Number
- CN202411291323.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to realize real-time monitoring of acrylonitrile gas, especially in complex environments. Traditional detection methods are expensive and complex in processes, electrochemical sensors are expensive and have short lifespans, and cross-interference problems exist.
By dissolving the precursor containing Al and Zn in an acid solvent, sintering at high temperature to form a Zn-doped γ-Al2O3 matrix material, and evenly dispersing Pt and Pd particles on its surface to form acrylonitrile cracking catalysis Materials, combined with electrochemical sensors to detect nitric oxide concentration to achieve indirect detection of acrylonitrile gas.
Real-time monitoring of acrylonitrile gas is achieved, the use of precious metals is reduced, the uniformity of catalytic active sites and the stability of materials is improved, the cost of raw materials is reduced, and the cross-interference problem in traditional methods is avoided.
Smart Images

Figure CN119236927A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of acrylonitrile gas detection, and more specifically to the technical field of a preparation method and a detection method of a material that can be used to indirectly detect acrylonitrile gas. The invention relates to a method for indirectly detecting acrylonitrile gas by applying thermal cracking of acrylonitrile gas. Background Art
[0002] Acrylonitrile (C3H3N), an organic compound, is a highly flammable and toxic substance. C3H3N may exist in various special places such as petroleum and petrochemical, pharmaceutical production workshops, chemical plants, and smelters. On-site monitoring of acrylonitrile gas and immediate alarm when the gas concentration exceeds the standard are the safety guarantee for operations in hazardous places.
[0003] At present, there are two methods for detecting acrylonitrile in the air: gas chromatography and the more accurate and direct gas chromatography-mass spectrometry. However, the high cost of using such methods and the complexity of the detection process make them unsuitable for real-time monitoring of acrylonitrile in complex environments. In addition, on-site gas detectors can detect gases quickly and accurately based on the working principles of different types of sensors, providing early warning for on-site operation safety. However, the electrochemical sensors that are currently effective for detecting acrylonitrile gas are not only expensive, but also have obvious problems such as short lifespan and cross-interference from other gases.
[0004] Based on the above situation, it is very necessary to carry out on-site early warning of acrylonitrile volatile gas. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problem of real-time indirect detection of acrylonitrile gas at the scene, and to provide a preparation method and a detection method of a material that can be used for indirect detection of acrylonitrile gas.
[0006] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:
[0007] One aspect of the present invention provides a method for preparing a material that can be used for indirect detection of acrylonitrile gas, comprising the following steps:
[0008] S1. Preparation of acrylonitrile catalytic material: dissolving an Al-containing precursor and a Zn-containing precursor in an excess acidic solvent to obtain a precursor raw material solution, heating and drying the precursor raw material solution to obtain a mixture containing Al and Zn, and sintering the mixture containing Al and Zn at a high temperature to obtain a Zn-doped γ-Al2O3 matrix material;
[0009] S2. Preparation of acrylonitrile cracking device: dissolving a soluble salt containing Pt and Pd in an appropriate amount of an acidic solvent and mixing it with the γ-Al2O3 matrix material prepared in step S1, heating and drying the mixture, and evenly mixing it with a binder to obtain a viscous slurry, which is then coated on a platinum wire with a spiral coil, and heating the platinum wire by supplying electricity at both ends, thereby in-situ sintering the platinum wire to form an acrylonitrile cracking device in which Zn, Pt and Pd are evenly dispersed in γ-Al2O3.
[0010] The present invention provides a method for preparing a catalytic material, wherein platinum (Pt) and palladium (Pd) particles are uniformly dispersed on the surface of a Zn-doped nanoscale γ-phase alumina (γ-Al2O3) matrix to ensure the long-term stability of the material structure and stable catalytic activity.
[0011] In one embodiment, in step S1, the Al-containing precursor is at least one of aluminum chloride (AlCl3), aluminum nitrate (Al(NO3)3), aluminum sulfate (Al(SO4)3), and hydrated aluminum oxide (Al2O3·nH2O). All of the above substances can be used as a source of porous and large specific surface area γ-Al2O3.
[0012] In one embodiment, in step S1, the Zn-containing precursor is at least one of zinc oxide (ZnO), zinc sulfate (ZnSO4), zinc chloride (ZnCl2), and zinc hydroxide (Zn(OH)2).
[0013] In one embodiment, in step S1, the acidic solvent is at least one of a diluted solution of sulfuric acid, hydrochloric acid, and nitric acid.
[0014] In one embodiment, in step S1, the heating and drying temperature is: the heating temperature is 50-100° C., and the heating time is 3-10 hours. Preferably, the heating temperature is 60-80° C., and the heating time is 4-6 hours.
[0015] High temperature sintering temperature and time: 500°C~900°C, calcination time 1~8h, more preferably, calcination temperature 550~700°C, calcination time is 2~5h.
[0016] In one embodiment, in step S2, the soluble salt of Pt is at least one of platinum dichloride and platinum tetrachloride;
[0017] The soluble salt of Pd is at least one of palladium chloride and palladium nitrate.
[0018] In one embodiment, in step S2, the acidic solution is at least one of dilute solutions such as sulfuric acid, hydrochloric acid, and nitric acid;
[0019] Adhesive solvent: preferably at least one of sodium carboxymethyl cellulose, sodium alginate and styrene-butadiene rubber.
[0020] In one embodiment, in step S2, the heating and drying temperature is: the heating temperature is 50-100° C., and the heating time is 2-6 hours; preferably, the heating temperature is 60-80° C., and the heating time is 2-4 hours.
[0021] High temperature sintering temperature and time: sintering temperature 350°C to 700°C, sintering time 3-5h. Preferably, a sintering temperature of 400 to 550°C can be selected to generate acrylonitrile cracking catalytic material in situ, i.e., acrylonitrile cracking device.
[0022] In one embodiment, in step S1, the molar ratio of aluminum ions to zinc ions in the aluminum-containing precursor and the zinc-containing precursor is 8 to 15:1, preferably 10 to 12:1;
[0023] In step S2, 0.5-4 parts by weight of a soluble salt of Pt and / or Pd is selected and mixed with 100 parts by weight of a γ-Al2O3 matrix material.
[0024] Another aspect of the present invention provides a method for indirectly detecting acrylonitrile gas, wherein the acrylonitrile cracking catalytic material prepared by the above-mentioned method for preparing a material for indirectly detecting acrylonitrile gas comprises the following steps:
[0025] The gas containing acrylonitrile is transported to the acrylonitrile cracking catalytic material in a high-temperature state at a rated flow rate to complete the automatic cracking of the acrylonitrile gas, and the acrylonitrile cracking catalytic material is detected to crack acrylonitrile to obtain nitric oxide, thereby achieving the purpose of indirect detection of acrylonitrile gas based on the detection of nitric oxide concentration, thereby realizing indirect detection of acrylonitrile gas.
[0026] The beneficial effects of the present invention are as follows:
[0027] The invention is reasonably designed, combines catalytic cracking with electrochemical sensor detection technology, prepares a catalytic material that can stably crack acrylonitrile, efficiently converts acrylonitrile to generate nitric oxide gas, and uses a nitric oxide sensor for detection, thereby realizing real-time monitoring of acrylonitrile leakage concentration.
[0028] 2. The acrylonitrile cracking catalytic material prepared by the method of the present invention adopts an excessive amount of acid solvent to uniformly mix Zn and Al-related substances, and obtains a γ-phase alumina matrix material uniformly doped with Zn particles through a primary sintering treatment. An appropriate amount of acid solvent can be used to obtain a mixture of Pt, Pd and γ-Al2O3 through a secondary sintering while ensuring that the soluble salts of Pt and Pd are completely dissolved. The Zn particles can be used as a structural additive to effectively avoid the agglomeration of γ-Al2O3 during the sintering process, maintain the dispersibility of γ-Al2O3, and improve the phase stability of the alumina matrix. In addition, compared with the catalysts prepared by the common impregnation method and coating method, this method can reduce the use of precious metals Pt and Pd, improve the dispersion uniformity of the precious metal elements, reduce the cost of raw materials, and make the catalytic active sites more uniform. In addition, by providing high temperature for secondary sintering through platinum wire power supply and calcining the catalyst precursor, γ-Al2O3-based catalytic materials can be prepared in situ and used as acrylonitrile cracking catalytic bead devices, ensuring that the internal microstructure of the γ-Al2O3 matrix is no longer damaged and can simultaneously meet the heating conditions for acrylonitrile cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 This is a scanning electron microscope (SEM) image of the catalyst prepared in Example 1.
[0031] Figure 2 This is the elemental analysis spectrum of the acrylonitrile cracking material prepared in Example 1. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and technical effects of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0033] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In some embodiments, a method for preparing a material that can be used to indirectly detect acrylonitrile gas is provided, including preparing an acrylonitrile catalytic material and preparing an acrylonitrile cracking device:
[0035] S1. Preparation of acrylonitrile catalytic material: dissolving an Al-containing precursor and a Zn-containing precursor in an excess acidic solvent to obtain a precursor raw material solution, heating and drying the precursor raw material solution to obtain a mixture containing Al and Zn, and sintering the mixture containing Al and Zn at a high temperature to obtain a Zn-doped γ-Al2O3 matrix material;
[0036] In step S1, the Al-containing precursor is at least one of aluminum chloride (AlCl3), aluminum nitrate (Al(NO3)3), aluminum sulfate (Al(SO4)3) and hydrated aluminum oxide (Al2O3·nH2O). All of the above substances can be used as a source of porous and large specific surface area γ-Al2O3.
[0037] In step S1, the Zn-containing precursor is at least one of zinc oxide (ZnO), zinc sulfate (ZnSO4), zinc chloride (ZnCl2), and zinc hydroxide (Zn(OH)2).
[0038] In step S1, the acidic solvent is at least one of a diluted solution of sulfuric acid, hydrochloric acid, and nitric acid.
[0039] In step S1, heating and drying temperature: heating temperature is 50-100°C, heating time is 3-10h, preferably, heating temperature is 60-80°C, heating time is 4-6h;
[0040] High temperature sintering temperature and time: 500°C~900°C, calcination time 1~8h, more preferably, calcination temperature 550~700°C, calcination time is 2~5h.
[0041] In step S1, the molar ratio of aluminum ions to zinc ions in the aluminum-containing precursor and the zinc-containing precursor is 8-15:1, preferably 10-12:1.
[0042] S2. Preparation of acrylonitrile cracking device: dissolving a soluble salt containing Pt and Pd in an appropriate amount of an acidic solvent and mixing it with the γ-Al2O3 matrix material prepared in step S1, heating and drying the mixture, and evenly mixing it with a binder to obtain a viscous slurry, which is then coated on a platinum wire with a spiral coil, and heating the platinum wire by supplying electricity at both ends, thereby in-situ sintering the platinum wire to form an acrylonitrile cracking device in which Zn, Pt and Pd are evenly dispersed in γ-Al2O3.
[0043] In step S2, the soluble salt of Pt is at least one of platinum dichloride and platinum tetrachloride;
[0044] The soluble salt of Pd is at least one of palladium chloride and palladium nitrate.
[0045] In step S2, the acidic solution is at least one of dilute solutions such as sulfuric acid, hydrochloric acid, and nitric acid;
[0046] Adhesive solvent: preferably at least one of sodium carboxymethyl cellulose, sodium alginate and styrene-butadiene rubber.
[0047] In step S2, the heating and drying temperature is: the heating temperature is 50-100°C, and the heating time is 2-6 hours; preferably, the heating temperature is 60-80°C, and the heating time is 2-4 hours.
[0048] High temperature sintering temperature and time: sintering temperature 350°C to 700°C, sintering time 3-5h. Preferably, a sintering temperature of 400 to 550°C can be selected to generate acrylonitrile cracking catalytic material in situ, i.e., acrylonitrile cracking device.
[0049] In step S2, 0.5-4 parts by weight of a soluble salt of Pt and / or Pd is selected and mixed with 100 parts by weight of a γ-Al2O3 matrix material.
[0050] In this scheme, platinum (Pt) and palladium (Pd) particles are uniformly dispersed on the surface of a Zn-doped nanoscale γ-phase alumina (γ-Al2O3) matrix to ensure the long-term stability of the material structure and stable catalytic activity.
[0051] In some embodiments, a method for indirectly detecting acrylonitrile gas is provided, wherein the acrylonitrile cracking catalytic material prepared by the above-mentioned method for preparing a material that can be used for indirectly detecting acrylonitrile gas comprises the following steps:
[0052] The gas containing acrylonitrile is transported to the acrylonitrile cracking catalytic material in a high-temperature state at a rated flow rate to complete the automatic cracking of the acrylonitrile gas, and the acrylonitrile cracking catalytic material is detected to crack acrylonitrile to obtain nitric oxide, thereby achieving the purpose of indirect detection of acrylonitrile gas based on the detection of nitric oxide concentration, thereby realizing indirect detection of acrylonitrile gas.
[0053] A specific example of the method for preparing a material that can be used for indirect detection of acrylonitrile gas is shown below:
[0054] Example 1
[0055] This embodiment provides a method for preparing a material that can be used to indirectly detect acrylonitrile gas, comprising the following steps:
[0056] 1) Prepare 20 ml of 2 mol / L nitric acid solution, weigh 3 g of aluminum hydroxide and slowly add it into the solution and stir evenly. Add 0.3 g of zinc oxide during continuous stirring to obtain a mixed solution.
[0057] 2) placing the mixed solution in a forced air drying oven and heating it at 80°C for 5 hours to obtain a dry mixture;
[0058] 3) Place the dry mixture in a tube furnace, heat it to 650°C at a heating rate of 5°C / min, keep it warm for 2.5 hours, cool it naturally, and grind it to obtain a catalyst matrix material;
[0059] 4) Weigh 0.1 g of platinum tetrachloride and palladium nitrate respectively and dissolve them in 20 ml of 0.2 mol / L nitric acid solution;
[0060] 5) Weigh 2 g of the catalytic matrix material and add it to 4 ml of nitric acid solution containing Pt and Pd and mix;
[0061] 6) placing the mixture in a forced air drying oven and heating it at 80° C. for 3 h to obtain a dry mixture;
[0062] 7) Add 1% sodium carboxymethyl cellulose solution to the dry mixture and grind evenly to form a sticky slurry;
[0063] 8) The slurry is coated on a spiral platinum wire and sintered by applying voltage at a sintering temperature of 400° C. for 4 hours to obtain an acrylonitrile cracking device, i.e., an acrylonitrile catalytic cracking bead, in situ on the platinum wire.
[0064] Figure 1 This is a scanning electron microscope (SEM) image of the acrylonitrile cracking catalytic material prepared in Example 1. Figure 1 It can be seen that the acrylonitrile cracking catalytic material prepared in Example 1 has an obvious porous structure of γ-Al2O3, the overall morphology is uniform, and the Pt and Pd components with main catalytic effects are uniformly dispersed on the surface and pores of γ-Al2O3, providing abundant active sites for acrylonitrile cracking catalysis.
[0065] Figure 2 The elemental analysis spectrum of the acrylonitrile cracking catalytic material prepared in Example 1 is as follows: Figure 2 It can be seen that zinc, platinum and palladium elements are successfully doped in the prepared acrylonitrile cracking material, and only a small amount of C and Na elements remain as the remaining components after sintering.
[0066] Table 1 Figure 2 Detailed data on the proportion of each element in the.
[0067] element weight% element% C 7.88 12.61 O 54.03 64.91 Na 0.26 0.22 Al 28.06 19.98 Pt 3.42 0.80 Pd 5.44 0.86 Zn 0.91 0.62
[0068] Example 2
[0069] This embodiment provides a method for preparing a material that can be used for indirect detection of acrylonitrile gas (changing the calcination temperature), comprising the following steps:
[0070] 1) Prepare 20 ml of nitric acid solution with a concentration of 2 mol / L, weigh 3 g of aluminum hydroxide and slowly add it into the solution and stir evenly, add 0.3 g of zinc oxide during continuous stirring to obtain a mixed solution;
[0071] 2) placing the mixed solution in a forced air drying oven and heating it at 80°C for 5 hours to obtain a dry mixture;
[0072] 3) Place the dry mixture in a tube furnace, heat it to 800°C at a heating rate of 5°C / min, keep it warm for 2.5 hours, cool it naturally, and grind it to obtain a catalyst matrix material;
[0073] 4) Weigh 0.1 g of platinum tetrachloride and palladium nitrate respectively and dissolve them in 20 ml of 0.2 mol / L nitric acid solution;
[0074] 5) Weigh 2 g of the catalytic matrix material and add it into 4 ml of nitric acid solution containing Pt and Pd and mix;
[0075] 6) placing the mixture in a forced air drying oven and heating it at 80° C. for 3 h to obtain a dry mixture;
[0076] 7) adding 1% sodium carboxymethyl cellulose solution to the dry mixture and grinding the mixture to form a viscous slurry;
[0077] 8) The slurry is coated on a spiral platinum wire and sintered by applying voltage at a sintering temperature of 400° C. for 4 hours to obtain an acrylonitrile cracking device, i.e., an acrylonitrile catalytic cracking bead, in situ on the platinum wire.
[0078] Example 3
[0079] This embodiment provides a method for preparing a material that can be used to indirectly detect acrylonitrile gas (changing the precursor material and the corresponding solvent):
[0080] 1) Prepare 20 ml of 0.5 mol / L hydrochloric acid solution, weigh 5 g of aluminum chloride and slowly add it into the solution and stir evenly. Add 0.5 g of zinc chloride during continuous stirring to obtain a mixed solution.
[0081] 2) The mixed solution was placed in a forced air drying oven and heated at 80° C. for 5 h to obtain a dry mixture.
[0082] 3) Place the dry mixture in a tube furnace, heat it to 650°C at a heating rate of 5°C / min, keep it warm for 2.5 hours, cool it naturally, and grind it to obtain a catalyst matrix material.
[0083] 4) Weigh 0.1g of platinum dichloride and palladium chloride respectively and dissolve them in 20ml of 0.1mol / L hydrochloric acid solution.
[0084] 5) Weigh 2 g of the catalytic matrix material and add it to 4 ml of the hydrochloric acid solution containing Pt and Pd and mix.
[0085] 6) The mixture was placed in a forced air drying oven and heated at 80° C. for 3 h to obtain a dry mixture.
[0086] 7) Add 1% sodium carboxymethyl cellulose solution to the dry mixture and grind evenly to form a viscous slurry.
[0087] 8) The slurry is coated on a spiral platinum wire and sintered by applying voltage at a sintering temperature of 400° C. for 4 hours to obtain an acrylonitrile cracking device, i.e., an acrylonitrile catalytic cracking bead, in situ on the platinum wire.
[0088] Example 4
[0089] This embodiment provides a method for preparing a material that can be used to indirectly detect acrylonitrile gas (changing the content of platinum and palladium):
[0090] 1) Prepare 20 ml of nitric acid solution with a concentration of 2 mol / L, weigh 3 g of aluminum hydroxide and slowly add it into the solution and stir evenly, add 0.3 g of zinc oxide during continuous stirring to obtain a mixed solution;
[0091] 2) placing the mixed solution in a forced air drying oven and heating it at 80°C for 5 hours to obtain a dry mixture;
[0092] 3) Place the dry mixture in a tube furnace, heat it to 650°C at a heating rate of 5°C / min, keep it warm for 2.5 hours, cool it naturally, and grind it to obtain a catalyst matrix material;
[0093] 4) Weigh 0.2g of platinum tetrachloride and palladium nitrate respectively and dissolve them in 20ml of 0.2mol / L nitric acid solution;
[0094] 5) Weigh 2 g of the catalytic matrix material and add it into 4 ml of nitric acid solution containing Pt and Pd and mix;
[0095] 6) placing the mixture in a forced air drying oven and heating it at 80° C. for 3 h to obtain a dry mixture;
[0096] 7) Add 1% sodium carboxymethyl cellulose solution to the dry mixture and grind evenly to form a sticky slurry;
[0097] 8) The slurry is coated on a spiral platinum wire and sintered by applying voltage at a sintering temperature of 400°C for 4 hours to obtain an acrylonitrile catalytic cracking material, i.e., an acrylonitrile catalytic cracking bead, on the platinum wire. A specific example of a method for indirect detection of acrylonitrile gas is shown as follows:
[0098] Embodiment 5:
[0099] A voltage is applied to both ends of the acrylonitrile catalytic cracking beads prepared in Example 1 so that the catalytic cracking beads reach a high temperature of about 400°C after full combustion, and acrylonitrile standard gas is introduced at a flow rate of 0.15L / min to detect the acrylonitrile cracking catalytic material for cracking acrylonitrile to produce nitric oxide, thereby achieving the purpose of indirect detection of acrylonitrile gas based on the detection of nitric oxide concentration, thereby realizing indirect detection of acrylonitrile gas.
Claims
1. A method for preparing a material that can be used for indirect detection of acrylonitrile gas, characterized in that: The steps include: S1. Preparation of acrylonitrile catalytic material: dissolving an Al-containing precursor and a Zn-containing precursor in an excess acidic solvent to obtain a precursor raw material solution, heating and drying the precursor raw material solution to obtain a mixture containing Al and Zn, and sintering the mixture containing Al and Zn at a high temperature to obtain a Zn-doped γ-Al2O3 matrix material; S2. Preparation of acrylonitrile cracking device: dissolving a soluble salt containing Pt and Pd in an appropriate amount of an acidic solvent and mixing it with the γ-Al2O3 matrix material prepared in step S1, heating and drying the mixture, and evenly mixing it with a binder to obtain a viscous slurry, which is then coated on a platinum wire with a spiral coil, and heating the platinum wire by supplying electricity at both ends, thereby in-situ sintering the platinum wire to form an acrylonitrile cracking device in which Zn, Pt and Pd are evenly dispersed in γ-Al2O3.
2. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S1, the Al-containing precursor is at least one of aluminum chloride (AlCl3), aluminum nitrate (Al(NO3)3), aluminum sulfate (Al(SO4)3) and hydrated aluminum oxide (Al2O3·nH2O).
3. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S1, the Zn-containing precursor is at least one of zinc oxide (ZnO), zinc sulfate (ZnSO4), zinc chloride (ZnCl2), and zinc hydroxide (Zn(OH)2).
4. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S1, the acidic solvent is at least one of a diluted solution of sulfuric acid, hydrochloric acid, and nitric acid.
5. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S1, heating and drying temperature: heating temperature 50~100℃, heating time 3~10h; High temperature sintering temperature and time: 500℃~900℃, calcination time 1~8h.
6. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S2, the soluble salt of Pt is at least one of platinum dichloride and platinum tetrachloride; The soluble salt of Pd is at least one of palladium chloride and palladium nitrate.
7. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S2, the acidic solution is at least one of sulfuric acid, hydrochloric acid, and nitric acid; The bonding solvent is at least one of sodium carboxymethyl cellulose, sodium alginate and styrene-butadiene rubber.
8. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S2, heating and drying temperature: heating temperature is 50-100°C. High temperature sintering temperature and time: sintering temperature 350℃~700℃, sintering time 3-5h.
9. The method for preparing a material for indirect detection of acrylonitrile gas according to claim 1, characterized in that: In step S1, the molar ratio of aluminum ions to zinc ions in the aluminum-containing precursor and the zinc-containing precursor is 8 to 15:1; In step S2, 0.5-4 parts by weight of a soluble salt of Pt and / or Pd is selected and mixed with 100 parts by weight of a γ-Al2O3 matrix material.
10. A method for indirectly detecting acrylonitrile gas, characterized in that: The acrylonitrile cracking catalytic material prepared by the method for preparing a material for indirect detection of acrylonitrile gas according to any one of claims 1 to 3 comprises the following steps: The gas containing acrylonitrile is transported to the acrylonitrile cracking catalytic material in a high-temperature state at a rated flow rate to complete the automatic cracking of the acrylonitrile gas, and the acrylonitrile cracking catalytic material is detected to crack acrylonitrile to obtain nitric oxide, thereby achieving the purpose of indirect detection of acrylonitrile gas based on the detection of nitric oxide concentration, thereby realizing indirect detection of acrylonitrile gas.